Binary and Ternary Blends of Polypropylene Types – Influence on the Homogeneity of Biaxial‐Oriented Films. Issue 1 (July 2016) - Schubert, Dirk W.; Kaschta, Joachim; Seidl, Stephan; Kunzelmann, Peter
Summary: Biaxial‐oriented polypropylene (BOPP) is one of the most used materials for industrial films and food packaging. In terms of environmental and economic issues, the reduction of the film thickness, increasing the homogeneity, enhancing the process efficiency and stability are in the focus of this work. A systematic investigation on the biaxial stretching process is presented in this study. Therefore, two commercial linear polypropylenes with different molar masses and a commercial long‐chain‐branched polypropylene were used to obtain binary and ternary blends to adjust the elongation behavior on the molecular level. The blending was carried out using a cast film process on a twin‐screw extruder. The cast films obtained, were investigated before and after biaxial stretching. The thickness distribution of the films, were used as a measure of the film homogeneity, before and after the film stretching process. It turns out that casting and biaxial stretching are competing steps with respect to the film homogeneity. The casting step is dominated by the extrusion behavior of the blends. With increasing amount of the long‐chain branched material extrusion flow instabilities appear leading to an irregular surface and to a poor film homogeneity. Contrarily, long‐chain branches promote a more homogeneous deformation during the biaxial stretching inducing strain hardening which leads to a self‐healing effect and thus to an improved film homogeneity. The homogeneity of the final stretched film depends on both, casting and stretching. Therefore, a desirable polymer blend recipe with a medium amount of long‐chain branches is revealed for the stretched film.